Mekanisme Molekuler Pemanfaatan Wolbachia terhadap Virus Dengue - Nugraha, Gita Rahmania (Universitas Malahayati, 2024)
ABSTRACT The incidence of dengue fever has increased drastically worldwide in recent decades. The increase in dengue fever shows that disease control programs are ineffective, new alternatives are needed. Wolbachia is used as a new alternative. This research aims to understand how the use of Wolbachia can influence the development of the dengue virus molecularly. This is a type of descriptive research with a qualitative approach. The research design is based on a systematic review study by collecting relevant journals indexed by Sinta and Google Scholar. The research results show that genetic manipulation of mosquitoes using Wolbachia bacteria can cause a decrease in virus copies and RNA copies with the mosquito's ability to block virus replication, all of which is related to cytoplasmic incompatibility. Wolbachia bacteria show potential as DENV biocontrol agents. This endosymbiotic bacteria, if integrated into the Aedes aegypti population, can reduce the ability of mosquitoes to spread the dengue fever virus. A comparison of four dengue fever isolates shows differences in the amount of RNA translated which affects the envelope protein E on the use of Wolbachia bacterial cells. Further studies are needed regarding the ratio of bases in RNA in dengue fever viruses. Keywords: Aedes aegypti, Dengue, Wolbachia ABSTRAK Insiden demam berdarah telah meningkat secara drastis di seluruh dunia dalam beberapa dekade terakhir. Meningkatnya penyakit demam berdarah menunjukkan bahwa program pengendalian penyakit tidak efektif, diperlukan alternatif baru. Wolbachia digunakan sebagai alternatif baru. Penelitian ini bertujuan untuk memahami bagaimana pemanfaatan Wolbachia dapat mempengaruhi perkembangan virus dengue secara molekuler. Merupakan jenis penelitian deskriptif dengan pendekatan kualitatif. Desain penelitian didasarkan pada studi systematic review dengan mengumpulkan jurnal - jurnal yang relevan terindeks Sinta dan Google Scholar. Hasil penelitian menunjukkan bahwa manipulasi genetik nyamuk menggunakan bakteri Wolbachia dapat menyebabkan penurunan salinan virus dan RNA copy dengan kemampuan nyamuk dalam memblokir replikasi virus yang mana semuanya berkaitan dengan ketidakcocokan sitoplasma. Bakteri Wolbachia menunjukkan potensi sebagai agen biokontrol DENV. Bakteri endosimbiotik ini jika diintegrasikan ke dalam populasi Aedes aegypti dapat menurunkan kemampuan nyamuk dalam menyebarkan virus demam berdarah. Dari perbandingan empat isolat demam berdarah menunjukan perbedaan jumlah RNA yang ditranslasikan sehingga mempengaruhi envelope protein E terhadap penggunaan sel bakteri Wolbachia. Diperlukan pengkajian lebih lanjut mengenai perbandingan basa di RNA pada virus demam berdarah. Kata Kunci: Aedes Aegypt, Dengue, Wolbachia